Headache in the paediatric population: the role of the ophthalmologist - Degrassi, Marta; Tonetto, Stefania; Michieletto, Paola; Dalena, Paolo; Barbi, Egidio; Pensiero, Stefano (Frontiers in Pediatrics, 2025)
IntroductionHeadache is a very common pathology in pediatric age, but the responsibility of ophthalmological factors in determining headache may be underestimated.AimIdentify how headache presents and determine the prevalence of the different causes in children; investigate the role of the ophthalmologist and of the ophthalmic diagnostic investigations in the diagnosis and treatment of pediatric headache.Methods101 children, aged 4–18 years, with non-traumatic headache were included in the study. Each child underwent a questionnaire regarding headache characteristics and all the clinical and instrumental examinations necessary to reach the diagnosis.ResultsMigraine was the most common form (28.7%), followed by headache associated with inadequate refractive error. (HARE, 23.7%), tension-type headache (17.8%), strabismus (16.8%), intracranial hypertension (6.9%), digital eye strain (5.9%). Myopia was the most prevalent type of HARE (50%). Strabismus headache was present especially in intermittent exotropia (41.2%) and convergence insufficiency (35.3%).DiscussionHARE and strabismus, despite the latter is not included in the final version of the International Classification of Headache Disorders, can cause frontal headache in many cases.ConclusionOcular causes are a frequent cause of a relevant percentage of pediatric headaches.